Diffusion of Inorganic Materials in Soil - Kirk, G.J.D. (Royal Society, 1990)
Long-established theory concerning the diffusion of solutes in soil is described, with particular reference to the means by which pH changes are propagated through soil by acid-base transfer. The application of the theory is then demonstrated by way of models of the reaction with soil or two important fertilizer materials (urea and rock phosphate) and a model of the diffusion and oxidation of ferrous iron in the rhizosphere of lowland rice. Experimental verifications of the urea and rock phosphate models are given, in which reactant concentration profiles in the soil are compared with model predictions based on independently measured parameter values. No parameter-fitting is used. A sensitivity analysis of the urea model shows how loss of urea-derived nitrogen by ammonia volatilization depends on fertilizer, soil and atmospheric parameters. A sensitivity analysis of the rock phosphate model shows how the rate of rockphosphate dissolution and the amount of dissolved phosphorus taken up by plant roots depend on fertilizer, soil and plant parameters including acid-base release by roots. A sensitivity analysis of the iron diffusion and oxidation model shows how rice roots may greatly alter chemical, conditions in the soil near them, with major implications for nutrient and toxin transformations.